Supporting advanced dementia in people with Down syndrome and other intellectual disability: consensus statement of the International Summit on Intellectual Disability and Dementia*. Issue 7 (20th May 2018) - McCarron, M.; McCallion, P.; Coppus, A.; Fortea, J.; Stemp, S.; Janicki, M.; Wtachman, K.
Abstract: Background: The International Summit on Intellectual Disability and Dementia (Glasgow, Scotland; October 2016) noted that advanced dementia can be categorised as that stage of dementia progression characterised by significant losses in cognitive and physical function, including a high probability of further deterioration and leading to death. Method: The question before the Summit was whether there were similarities and differences in expressions of advanced dementia between adults with intellectual disability (ID) and adults in the general population. Results: The Summit noted challenges in the staging of advanced dementia in people with ID with the criteria in measures designed to stage dementia in the general population heavily weighted on notable impairment in activities of daily living. For many people with an ID, there is already dependence in these domains generally related to the individuals pre‐existing level of intellectual impairment, that is, totally unrelated to dementia. Hence, the Summit agreed that as was true in achieving diagnosis, it is also imperative in determining advanced dementia that change is measured from the person's prior functioning in combination with clinical impressions of continuing and marked decline and of increasing co‐morbidity, including particular attention to late‐onset epilepsy in people with Down syndrome. It was further noted that quality care planning must recognise the greater likelihood of physical symptoms, co‐morbidities, immobility and neuropathological deterioration. Conclusions: The Summit recommended an investment in research to more clearly identify measures of person‐specific additional decline for ascertaining advanced dementia, inform practice guidelines to aid clinicians and service providers and identify specific markers that signal such additional decline and progression into advanced dementia among people with various levels of pre‐existing intellectual impairment.